Design and Evaluation of Dental and Oral Health Education Using Design Thinking - Blolong, Damiana Trivinita L; Wibowo, Merlinda (Telematika, 2024)
Purpose: To design a learning  for dental and oral health by applying the Design thinking method.Design/method/approach: using the Design thinking method which has several processes such as Empathize, Define, Ideate, Prototype, and Test.Finding/Result:  Design as a learning media for dental and oral health that is adapted to what is needed by users.Originality/state of the art: Designing a learning media website using the design thinking method and then evaluating to measure the quality of the system using the System Usability Scale method.